Comparison of various techniques for the extraction and determination of antioxidants in plants. Issue 7 (7th March 2014) - Bajerová, Petra; Adam, Martin; Bajer, Tomáš; Ventura, Karel
<x xml:space="preserve">Abstract</x> The following extraction techniques have been used for extracting antioxidants (apigenin, coumarin, esculetin, umbelliferone, bergapten, quercetin, rutin, scopoletin and xanthotoxin) from plant material: supercritical fluid extraction, pressurized liquid extraction, extraction by means of Soxhlet apparatus, ultrasonic extraction in ultrasonic bath, and by means of ultrasonic probe. The analytical method based on HPLC−UV detection for the determination of selected antioxidants was developed. For all extracts the antioxidant capacity based on the reduction of free 2, 2‐diphenyl‐1‐picrylhydrazyl radical was also determined. Comparing all results the ultrasonic probe method using 0.75 g of sample extracted by 50 mL of acetonitrile in water (30%, v/v) for 25 min at room temperature and with amplitude at 60% (equal to 90 W) without pulsation was evaluated as the best tool. The most significant indicator demonstrating this statement is the antioxidant capacity expressed as gallic acid equivalent where the ultrasonic probe method showed the best results in 10 of 16 samples. Also the operability of ultrasonic probe extraction method compared to other tested methods is more favorable.